The Effectiveness of a Scientific Approach in Improving Passing Ability in Volleyball Games at the Vuttisat Vittanuson School in Thailand - Radhin Miftah Shiddiq; Oman Hadiana; Hana Astria Nur; Nanan Abdul Manan; Casnan Casnan (Physical Activity Journal (PAJU), 2023)
Learning the game of volleyball at the Vuttisat Vittanuson school in Thailand, especially in terms of lower passing ability, still needs to improve. Applying the learning model provided by physical education teachers is still conventional, so it cannot build the effectiveness of student learning outcomes. This research aims to determine the effectiveness of a scientific approach on students volleyball passing abilities. This research is quasi experimental research with a Pretest Posttest Group Design research design. The population in this study were Mattayom 5 students at Vuttisat Vittayanuson School and a sample of 30. The instrument in this research is a volleyball passing ability test. The research results showed that based on the pretest and posttest scores, there was a significant increase. It is known that there is a difference in the positive influence of applying a scientific approach to students' passing ability in volleyball